Combining Brain Computer Interfaces with Vision for Object Categorization - Kapoor, Ashish; Shenoy, Pradeep; Tan, Desney (IEEE Conference on Computer Vision and Pattern Recognition (CVPR) 2008, 2008)
Human-aided computing proposes using information measured directly from the human brain in order to perform useful tasks. In this paper, we extend this idea by fusing computer vision-based processing and processing done by the human brain in order to build more effective object categorization systems. Speciﬁcally, we use an electroencephalograph (EEG) device to measure the subconscious cognitive processing that occurs in the brain as users see images, even when they are not trying to explicitly classify them. We present a novel framework that combines a discriminative visual category recognition system based on the Pyramid Match Kernel (PMK) within formation derived from EEG measurements as users view images. We propose a fast convex kernel alignment algorithm to effectively combine the two sources of information. Our approach is validated with experiments using real-world data, where we show signiﬁcant gains in classiﬁcation accuracy. We analyze the properties of this information fusion method by examining the relative contributions of the two modalities, the errors arising from each source, and the stability of the combination in repeated experiments.